Formulating Ether-Based Electrolytes for Highly Reversible Sodium Metal Anodes at High Temperatures - Xiuyun Ren; Yanmei Wu; Xijie Chen; Liang Hu; Yu Zhao; Tao Zhang; Bingcheng Ge; Xiaoqi Sun; Xiaoliang Yu (Energy Material Advances)
Battery systems enabling sustainable high energy output at elevated temperatures are highly desirable, especially in high-temperature (HT) environments or hot regions. Sodium metal batteries are attractive next-generation battery technologies with low production costs and high energy densities. The exacerbated detrimental side reactions between the sodium metal anode and the liquid electrolyte at HT, however, reduce sodium plating/stripping reversibility and shorten the cycle life. Ether-based electrolytes are highly compatible with the sodium metal anode, promising good HT electrochemical performances. Nonetheless, the correlation between the molecular structures of ether solvents and HT sodium reversibility has been poorly established because of the complex interfacial reactions. In this study, conventionally used cyclic and linear ethers have been paired with fluorine-rich sodium salt to formulate electrolytes for systematic study. We have revealed that linear ethers outperform cyclic ethers at HT because of their improved thermal stability. Among them, the electrolyte based on diglyme with an appropriate molecular structure delivers the best performance. It strikes a balance in the coordination strength between Na+ and the solvent, which ensures adequate participation of anions in the solvation sheath while reducing the solvent’s electrochemical activity for reductive decomposition at HT. Consequently, it induces the formation of an inorganic-rich solid–electrolyte interphase with compositional uniformity, excellent ionic conductivity, and high mechanical strength. Thus, a high sodium plating/stripping coulombic efficiency of 99.9% has been achieved at a high current density of 5 mA·cm−2. As-formulated anode-free sodium metal batteries maintain 80% of the initial capacity after 150 charge/discharge cycles at 60 °C.